2021
DOI: 10.1101/2021.03.07.434282
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Single cell analysis of the aging female hypothalamus

Abstract: Alterations in metabolism, sleep patterns, body composition, and hormone status are all key features of aging. The hypothalamus is a well-conserved brain region that controls these homeostatic and survival-related behaviors. Despite the importance of this brain region in healthy aging, little is known about the intrinsic features of hypothalamic aging. Here, we utilize single nuclei RNA-sequencing to assess the transcriptomes of 22,718 hypothalamic nuclei from young and aged female mice. We identify cell type… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 115 publications
(159 reference statements)
0
1
0
Order By: Relevance
“…The expression of Tyrosine Hydroxylase (TH) was characteristic of DaNs (Cluster 17), which encode rate-limiting enzymes in catecholamine synthesis and are involved in the conversion of tyrosine to dopamine (Garritsen et al, 2023) (Supplementary Figure S3I). Some were uncommon, such as N-deacetylase and N-sulfotransferase 4 (Ndst4) (markers of deep neurons), which was highly expressed in Cluster 9 (Cid et al, 2021); B230323A14Rik (a long noncoding RNA in neurons), which was highly expressed in Cluster 8 (Hajdarovic et al, 2022); and Cadherin-23 (Cdh23) (involved in the differentiation of neurons), which was highly expressed in Cluster 16 (Lord and Cruchaga, 2014) (Supplementary Figures 3J-L). Less abundant cell types were also observed, including Endothelial cells (Fms Related Receptor Tyrosine Kinase 1, Flt1), Ependymal cells (Sperm Associated Antigen 16, Spag16), and Fibroblasts (EYA Transcriptional Coactivator and Phosphatase 2, Eya2) (Supplementary Figures S3M-O).…”
Section: Single-nucleus Transcriptome Profiling To Identify Cell Popu...mentioning
confidence: 99%
“…The expression of Tyrosine Hydroxylase (TH) was characteristic of DaNs (Cluster 17), which encode rate-limiting enzymes in catecholamine synthesis and are involved in the conversion of tyrosine to dopamine (Garritsen et al, 2023) (Supplementary Figure S3I). Some were uncommon, such as N-deacetylase and N-sulfotransferase 4 (Ndst4) (markers of deep neurons), which was highly expressed in Cluster 9 (Cid et al, 2021); B230323A14Rik (a long noncoding RNA in neurons), which was highly expressed in Cluster 8 (Hajdarovic et al, 2022); and Cadherin-23 (Cdh23) (involved in the differentiation of neurons), which was highly expressed in Cluster 16 (Lord and Cruchaga, 2014) (Supplementary Figures 3J-L). Less abundant cell types were also observed, including Endothelial cells (Fms Related Receptor Tyrosine Kinase 1, Flt1), Ependymal cells (Sperm Associated Antigen 16, Spag16), and Fibroblasts (EYA Transcriptional Coactivator and Phosphatase 2, Eya2) (Supplementary Figures S3M-O).…”
Section: Single-nucleus Transcriptome Profiling To Identify Cell Popu...mentioning
confidence: 99%
“…To date, there is no evidence on the role of the hypothalamus in humans in aging. Recent rodent studies, however, identified the hypothalamus also as a key player in the aging process [16][17][18], suggesting that it could be involved in alterations of endocrine and metabolic processes in age, leading to more wide-spread aging effects by inducing inflammatory signaling. Hence, if hypothalamic microstructure is compromised by physical health or metabolic dysfunction in age, it could possibly affect the brain aging process.…”
Section: Introductionmentioning
confidence: 99%
“…The expression of Tyrosine Hydroxylase (TH) was characteristic of DaNs (Cluster 17), which encode rate-limiting enzymes in catecholamine synthesis and are involved in the conversion of tyrosine to dopamine (Garritsen et al, 2023) (Supplementary Figure S3I). Some were uncommon, such as N-deacetylase and N-sulfotransferase 4 (Ndst4) (markers of deep neurons), which was highly expressed in Cluster 9 (Cid et al, 2021); B230323A14Rik (a long noncoding RNA in neurons), which was highly expressed in Cluster 8 (Hajdarovic et al, 2022); and Cadherin-23 (Cdh23) (involved in the differentiation of neurons), which was highly expressed in Cluster 16 (Lord and Cruchaga, 2014) (Supplementary Figures 3J-L). Less abundant cell types were also observed, including Endothelial cells (Fms Related Receptor Tyrosine Kinase 1, Flt1), Ependymal cells (Sperm Associated Antigen 16, Spag16), and Fibroblasts (EYA Transcriptional Coactivator and Phosphatase 2, Eya2) (Supplementary Figures S3M-O).…”
Section: Single-nucleus Transcriptome Profiling To Identify Cell Popu...mentioning
confidence: 99%